Prosecutor's Intelligence Functions in Preventing Corruption: Strategic Development Security Technical Guideline Perspective - Andri Dharma; Madiasa Ablisar; Mahmud Mulyadi; Mirza Nasution (Dialogia Iuridica, 2023)
Corruption crimes are cracked down not only by repressive efforts but also by preventive efforts. The Indonesian Public Prosecutor's Office has several stages of preventive efforts to carry out its intelligence functions. Indonesia's Attorney General's Office has introduced a new program called Security for Strategic Development - Regional Investment in implementing intelligence functions. The issue is what the legal status of the Technical Guidelines on Security for Strategic Development and Regional Investments of the Indonesian Public Prosecutor's Office in Anti-Corruption will be in terms of legal certainty. This study is a prescriptive legal study, descriptive analysis. A legal approach is used as the data is subject to various laws and regulations. Data collection through library and field research surveys accompanied by documentary study and interviews. Based on the qualitative analysis, the results show that the Strategic Development of the Indonesian Public Prosecutor's Office for Prevention of Corruption Crimes and Technical Guidelines for Security of Local Investments regulation was made by Law No.16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia, Law No.17 of 2011 concerning State Intelligence, as well as the Regulation of the Attorney General No.PER-006/A/JA/07/2017 concerning the Organization and Work Procedure of the Indonesian Prosecutor's Office does not include the authority to prevent corruption based on the 2004 Attorney General's Law. B-484/D/Dpp/03/2020, dated March 12, 2020, by adapting it to Law No.11 of 2021 concerning the Indonesian Attorney General's Office, to provide legal certainty to prevent corruption.